( D^3 + D^2 - 4D - 4) y = 3e^-4x -6
"( D^3 + D^2 - 4D - 4) y = 3e^{-4x -6}"
Auxiliary equation is: "m^3+m^2-4m-4=0\\\\"
"\\Rightarrow (m+2)(m-2)(m+1)=0\\\\\n\\Rightarrow m=2,-2,-1\\\\\\;\\\\\n\\therefore\\text{C.F.}=c_1e^{2x}+c_2e^{-2x}+c_3e^{-x}\\\\\\;\\\\\n\\text{P.I.}=\\dfrac{1}{f(D)}f(x)=\\dfrac{1}{f(D)}e^{-4x}(3e^{-6})\\\\\\;\\\\\n=e^{-4x}\\times\\dfrac{1}{f(D-4)}\\times(3e^{-6})\\\\\\;\\\\\n=\\dfrac{3e^{-4x-6}}{(D-2)(D-6)(D-3)}\\\\\\;\\\\\n=3e^{-4x-6}\\left[\\dfrac{1}{12(D-6)}-\\dfrac{1}{3(D-3)}+\\dfrac{1}{4(D-2)}\\right]\\\\\\;\\\\\n=3e^{-4x-6}\\left[\\dfrac{e^{6x}}{12}\\int e^{-6x}dx-\\dfrac{e^{3x}}{3}\\int e^{-3x}dx+\\dfrac{e^{2x}}{4}\\int e^{-2x}dx\\right]\\\\\\;\\\\\n=3e^{-4x-6}\\left[-\\dfrac{1}{72}+\\dfrac{1}{9}-\\dfrac{1}{8}\\right]\\\\\\;\\\\\n=-\\dfrac{e^{-4x-6}}{12}"
"\\therefore \\text{The complete solution is} :-\\\\\ny=\\text{C.F.+P.I}.=c_1e^{2x}+c_2e^{-2x}+c_3e^{-x}-\\dfrac{e^{-4x-6}}{12}"
So,
Comments
Leave a comment